Windows 11 for seniors in easy steps : for PCs, laptops and touch devices - Price, Michael, 1942-; Vandome, Nick (In easy steps., 2022)
"Windows 11 for Seniors in easy steps is written with older citizens in mind. It'll guide you through Windows 11, a step at a time, and covers all the key features"--Page 4 of cover.